Mekanisme Pelanggaran Pemilu di Bawaslu - Robenson, Michael Kennedy (Jurnal Pengabdi, 2024)
Every election law enforcement is handled by an institution or agency that has the authority to supervise and enforce laws related to elections. In many countries, this task is usually carried out by an electoral body or electoral commission which is independent and has the authority to regulate and supervise the electoral process, as well as to take action against law violations that occur during elections, and the police institution also plays an important role in dealing with criminal election violations that are election participants and volunteers.